Design of a New Engine Hood based on Lattice Structure for Pedestrian Protection. Issue 1 (July 2021) - Liu, Meng; Sun, Fuzhen; Wang, Baoming; Wang, Jianfeng; Yang, Na
Abstract: This paper designs four kinds of three-dimensional negative Poisson's ratio lattice structures, based on the two-dimensional concave hexagonal negative Poisson's ratio honeycomb structure. Different parameters are designed for simulation analysis and experimental research, and the influence of different parameters on Poisson's ratio is studied respectively. The main contents are as follows: Firstly, the three-dimensional solid model of lattice structure is established by modeling software, and the different structural parameters are determined, and the equivalent mechanical model is established. And according to the relevant structural parameters to establish the test scheme. Then, the finite element software is used to simulate the test core material with different parameters. According to the simulation results, the influence of different parameters on Poisson's ratio is found out. Then the crashworthiness of the test board with different parameters is simulated and analyzed. According to the results, the most suitable structure is selected and applied to the engine hood. Finally, the simulation experiment of collision between pedestrian head and engine hood is carried out. The results of this paper compare the performance of lattice sandwich panels with different parameter structures in different tests and select the optimal combination of structural parameters. The adjustment and optimization direction of the structure is put forward according to the test results.